PENGEMBANGAN MEDIA PEMBELAJARAN FLIP PDF PROFESSIONAL BERBASIS ANDROID PADA MATA PELAJARAN PENGELOLAAN BISNIS KONSTRUKSI DAN PROPERTI - Siska Hardiyanti; Fahmi Rizal (Jurnal Applied Science in Civil Engineering, 2022)
This research was appointed because the number of students who got low scores was due to changes in the learning system at the school, the unavailability of reference books and inadequate learning media in construction and property business management subjects. The purpose of this research is to find out the steps for making Flip PDF Professional learning media based on android that are valid and feasible. This research includes research and development with the DDD-E (Decide, Design, Develop, Evaluated) development model developed by Ivers & Barron. The subjects of this study were students of class XI BKP (Property Construction Business) SMK N 1 Bukittinggi semester 1. The data collection instrument was taken using a questionnaire given to material experts, media experts, teachers and students to test the level of validity of the Android-based Flip PDF Professional learning media developed. The results showed that the level of validity of the learning media by the material expert validator was 0.97 in the valid category, the assessment by the media expert validator was 0.93 in the valid category, the evaluation by the teacher with a value of 0.96 was in the valid category and the evaluation by the students with a value of 0.80 which falls into the valid category. To assess the feasibility of the media seen from the evaluation of student learning outcomes, the results of hypothesis testing using the t-test state that t-count is greater than t-table (6.84 > 2.01), out of 24 students who did the posttest the scores of all students increased. , the average learning outcomes before using learning media O1 = 54.58 and learning outcomes after using learning media O2 = 72.29. It can be concluded that the Android-based Flip PDF Professionallearning media that was developed is valid and feasible to be used as a learning media for construction and property business management.